Allosteric Modulation of Beta1 Integrin Function Induces Lung Tissue Repair - Rehab AlJamal-Naylor; Linda Wilson; Susan McIntyre; Fiona Rossi; Beth Harrison; Mark Marsden; David J. Harrison (Hindawi Limited, 2012)
The cellular cytoskeleton, adhesion receptors, extracellular matrix composition, and their spatial distribution are together fundamental in a cell's balanced mechanical sensing of its environment. We show that, in lung injury, extracellular matrix-integrin interactions are altered and this leads to signalling alteration and mechanical missensing. The missensing, secondary to matrix alteration and cell surface receptor alterations, leads to increased cellular stiffness, injury, and death. We have identified a monoclonal antibody against β1 integrin which caused matrix remodelling and enhancement of cell survival. The antibody acts as an allosteric dual agonist/antagonist modulator of β1 integrin. Intriguingly, this antibody reversed both functional and structural tissue injury in an animal model of degenerative disease in lung.